Reflections on Criminal Compliance: Entrevista al Dr. Alain Casanovas Ysla - Chanjan Documet, Rafael (2019)
The purpose of the interview is to reflect on some aspects of Criminal Compliance, as well as to indicate how this tool contributes in the fight against  orruption and Money Laundering, and the challenges that this figure currently has.